Advances in Gammalloy Materials–Processes–Application Technology: Successes, Dilemmas, and Future - Kim, Young-Won; Kim, Sang-Lan (JOM (1989), 2018)
For the last several years, gamma titanium aluminide ( γ -TiAl)-based alloys, called “gammalloys,” in specific alloy-microstructure forms began to be implemented in civil aero-engines as cast or wrought low-pressure turbine (LPT) blades and in select ground vehicle engines as cast turbocharger rotors and wrought exhaust valves. Their operation temperatures are approximately up to 750°C for LPT blades and around 1000°C for turbocharger rotors. This article critically assesses current engineering gammalloys and their limitations and introduces eight strengthening pathways that can be adopted immediately for the development of advanced, higher temperature gammalloys. Intelligent integration of the pathways into the emerging application-specific research and development processes is emphasized as the key to the advancement of the gammalloy technology to the next higher engineering performance levels.